2020
DOI: 10.3390/cancers12082073
|View full text |Cite
|
Sign up to set email alerts
|

Examination of Prognostic Factors Affecting Long-Term Survival of Patients with Stage 3/4 Gallbladder Cancer without Distant Metastasis

Abstract: In advanced gallbladder cancer (GBC) radical resection, if multiple prognostic factors are present, the outcome may be poor; however, the details remain unclear. To investigate the poor prognostic factors affecting long-term surgical outcome, we examined 157 cases of resected stage 3/4 GBC without distant metastasis between 1985 and 2017. Poor prognostic factors for overall survival and treatment outcomes of a number of predictable preoperative poor prognostic factors were evaluated. The surgical mortality was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 43 publications
(49 reference statements)
1
12
0
Order By: Relevance
“…Some studies have suggested that elevated carbohydrate antigen 19-9 (CA19-9) and carcinoembryonic antigen (CEA) were associated with the poor prognosis of GBC [3,4]. Other clinicopathological characters including positive surgical margin, lympho-vascular invasion, perineural invasion, and liver invasion were also considered as the risk factors for GBC patients prognosis [5][6][7]. Nevin staging system was simple and convenient for surgeons to evaluate the GBC patients and approximately predicted the GBC prognosis [8].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have suggested that elevated carbohydrate antigen 19-9 (CA19-9) and carcinoembryonic antigen (CEA) were associated with the poor prognosis of GBC [3,4]. Other clinicopathological characters including positive surgical margin, lympho-vascular invasion, perineural invasion, and liver invasion were also considered as the risk factors for GBC patients prognosis [5][6][7]. Nevin staging system was simple and convenient for surgeons to evaluate the GBC patients and approximately predicted the GBC prognosis [8].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the prognostic factors for resected advanced GBC have been reported to include excessive blood loss [ 19 ], poor histology [ 19 ], N stage [ 20 ], ≥ 4 regional lymph node metastases [ 19 ], liver invasion [ 20 ], and R1 resection [ 20 ]. However, the multivariate analyses of these reports did not include prognostic factors for distant metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Liver invasion of 5 mm or more, invasion of the left margin or the entire area of the hepatoduodenal ligament, and four or more regional lymph node metastases are poor prognostic factors for GBC, even in patients without distant metastasis [ 19 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Liver invasion of 5 mm or more, invasion of the left margin or the entire area of the hepatoduodenal ligament, and four or more regional lymph node metastases are poor prognostic factors for GBC, even in patients without distant metastasis [19,31]. In our univariate analyses of patients with resected GBC and liver metastasis, those who underwent minor hepatectomy, those who had less blood loss, those with less surgery time, those with papillary type histology, those with T2 stage, those with post-operative morbidity of Clavien-Dindo classi cation ≤ 2, and those who received adjuvant chemotherapy showed more favorable outcomes (Table 3).…”
Section: Discussionmentioning
confidence: 99%